Is it True Perceived Fairness can Improve Employee Performance ? - Khotob, Umar Bin; Marlien, R.A. (Universitas Muhammadiyah Sorong, 2024)
The performance of the State Civil Service Apparatus can be used as a benchmark to determine the qualifications and competence of government employees, as a measure of public trust in the government. The purpose of this study was to determine the effect of psychological capital and Person Organization Fit on performance by moderating perceptions of fairness at the Pati District Health Office. This research was conducted on employees at the Pati District Health Office with a population of 107 people. The sample takes the entire population to be used as a research sample. Data analysis used validity test with matrix components, reliability test with Cronbach alpha, multiple regression analysis, t test and r2 test with adjust r2 and moderation test. The results of the study concluded that psychological capital had a positive and significant effect on the performance of employees at the Pati District Health Office. Person Organization Fit has a positive and significant effect on employee performance at the Pati District Health Office. The perception of justice is considered unable to moderate the variables of psychological capital and Person Organization Fit on performance in the Pati District Health Office.